2013
DOI: 10.1111/acer.12124
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Utilization in Medical Intensive Care Unit Survivors with Alcohol Withdrawal

Abstract: Background Rehospitalization is an important and costly outcome that occurs commonly in several diseases encountered in the medical intensive care unit (ICU). Although alcohol use disorders are present in 40% of ICU survivors and alcohol withdrawal is the most common alcohol-related reason for admission to an ICU, rates and predictors of rehospitalization have not been previously reported in this population. Methods We conducted a retrospective cohort study of medical ICU survivors with a primary or secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 39 publications
1
23
0
1
Order By: Relevance
“…Clark and colleagues conducted a retrospective cohort investigation of potential risk factors for death and acute care service utilization among medical ICU survivors admitted with alcohol withdrawal as a primary or secondary diagnosis (23), finding that a wide range of pre-ICU psychiatric diagnoses were independently associated with risk of rehospitalization. However, post-ICU psychiatric symptoms/disorders were not examined.…”
Section: Discussionmentioning
confidence: 99%
“…Clark and colleagues conducted a retrospective cohort investigation of potential risk factors for death and acute care service utilization among medical ICU survivors admitted with alcohol withdrawal as a primary or secondary diagnosis (23), finding that a wide range of pre-ICU psychiatric diagnoses were independently associated with risk of rehospitalization. However, post-ICU psychiatric symptoms/disorders were not examined.…”
Section: Discussionmentioning
confidence: 99%
“…Psychiatric comorbidities such as anxiety and depression also serve as a barrier to change. We previously demonstrated that the presence of anxiety, depression, or schizophrenia is independently associated with the time to death or first rehospitalization in medical ICU survivors with alcohol withdrawal [10]. Psychiatric comorbidities are more common in ICU survivors with an AUD and are associated with poor treatment compliance and worse treatment related outcomes in patients with an AUD [40].…”
Section: Discussionmentioning
confidence: 99%
“…Because of improvements in care, more than 80% of patients admitted to an ICU survive their hospitalization [9]. However, within one year of hospital discharge 44% of patients with an AUD who required ICU care are readmitted to the hospital or die [10]. As an enforced period of abstinence, admission to the hospital presents an ideal opportunity to address a patient’s underlying AUD and prevent future alcohol-related illness [11].…”
Section: Introductionmentioning
confidence: 99%
“…In a similarly young cohort without medical comorbidities, 4% of patients admitted to the ICU with alcohol withdrawal died within a year of hospital discharge while 40% were rehospitalized (10). Defining rates of rehospitalization for intoxicated patients may provide an opportunity to engage hospital systems and garner resources to improve outcomes.…”
mentioning
confidence: 99%
“…Therefore, substance use disorders, other psychiatric diagnoses (such as depression, anxiety, and bipolar disorder), or both are likely to be the underlying cause of intoxication. Prior studies demonstrate that ICU survivors with a dual diagnosis – an alcohol or substance use disorder plus another psychiatric diagnosis - are at the highest risk of recurrent morbidity and mortality following hospital discharge (10). Understanding whether these findings extend to patients admitted to the ICU with an acute intoxication may help identify those patients at highest risk of poor outcomes and, thus, focus resources following hospital discharge.…”
mentioning
confidence: 99%